PENGEMBANGAN SIMULASI “STRESS TEST” MENGGUNAKAN TES KRAEPELIN PADA TES PSIKOLOGI - Nur Indriani; Dwi Sakethi; Admi Syarif (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
Psychology test is intended to measure the differences between individuals to determine the reaction of the individual for a different situation which aims to assess someone's behavior. One of the most common psychological tests is the kraepelin test or newspaper test. Generally, this test uses several sheets of papers with numbers written in it. In this research, a web-based kraepelin test simulation was developed in order to accessible via computer or smartphone. User can do the test by selecting the kraepelin test menu, and then do the kraepelin test by adding two numbers. If the result of a sum was tens, write the last digit only within the specified time. The waterfall method is used to developed this system, where the stages consist of requirements analysis, design, implementation, and black box testing. The results of the black box test showed 80.88%. From this research, “stress test” simulation using kraepelin test on psychology has been developed to someone who will take a kraepelin test.